Answer: 2,-5 Step-by-step explanation: formula= -b+_√b^2 -4ac/2a a=1,b=3,c=-10 substituting the values in the formula -3+_√3^2-4*1*-10/2*1 =-3+_√9+49/2 =-3+_7/2 -3+7/2=2( -3+7=4,4/2=2) -3-7/2=-5 so the answer is 2,-5 Reply

Answer: formula = -b√ b²-4ac/2a Here b = 3 c = -10 a = 1 -3√ 9+80/2 -3±√ 89/2 Step-by-step explanation: hope it will help you… Try to followme so that I can help you in next example Reply

Answer:2,-5

Step-by-step explanation:formula= -b+_√b^2 -4ac/2a

a=1,b=3,c=-10

substituting the values in the formula

-3+_√3^2-4*1*-10/2*1

=-3+_√9+49/2

=-3+_7/2

-3+7/2=2( -3+7=4,4/2=2)

-3-7/2=-5

so the answer is 2,-5

Answer:formula = -b√ b²-4ac/2a

Here b = 3 c = -10 a = 1

-3√ 9+80/2

## -3±√ 89/2

Step-by-step explanation:hope it will help you… Try to followme so that I can help you in next example